PROBLEMS OF DETERMINING THE STATUS OF THE EMBRYO AS AN OBJECT OF CIVIL LAW - Babajanova Dinara Islamovna (PT. Antis International Publisher, 2025)
Objective: This study aims to analyze the challenges and ethical considerations in defining the legal status of embryos within civil law frameworks, focusing on cross-country legal approaches. Method: The analysis employs a comparative approach, reviewing legal doctrines and ethical perspectives from various jurisdictions to identify commonalities, differences, and controversies in regulating the legal status of embryos. Results: The findings reveal significant variations in how countries define and treat embryos legally, often influenced by cultural, religious, and moral considerations. Ethical concerns are deeply intertwined with reproductive rights and debates over the moral status of human life, further complicating consensus on the issue. Novelty: This study uniquely bridges the legal and ethical dimensions of embryo status, offering a nuanced perspective on the intersections of law, morality, and reproductive autonomy, providing a foundational reference for future interdisciplinary discourse.